Land Use Change and the Usefulness of the Periurban Landscape at the Guayllabamba River Basin in Ecuador - Abad-Auquilla, Katherine (2020)
[Introduction]: Territorial planning establishes processes that improve and align land morphology in order to achieve more compact and less diffuse cities. However, urban expansion has caused changes in land use and on terrestrial ecosystems affecting periurban areas located in the rural-urban interface, as a result of the arrival of new inhabitants and the development of industrial activities. [Objective]: This article analyzes the changes in land cover and the influence of the cultural ecosystem service of scenic beauty in the Guayllabamba River basin in Ecuador. [Methodology]: For this purpose, remote sensing tools and geographic information systems were used, satellite images were digitized, and an analysis of spectral bands was performed. [Results]: The development of urban settlement considerably increased in the study area, reducing forests and semi-natural areas due to an enlarged urbanization development. Still, agricultural territories maintained their activities in the area. [Conclusions]: The research also verified the usefulness of a landscape assessment as a process for the conservation of ecosystems since it establishes the impact levels to which a landscape is exposed.